المبادئ القانونية التي تحكم مفاوضات عقود التجارة الدولية - رندة قندوز; كوثر صالحي (My University, 2020)
Summary: International trade contract negotiations are based on many legal principles enshrined by the majority of comparative legislation and the same international rules in order to regulate the relationship between the negotiating parties freedom of negotiation ", the most prominent of which is the principle of freedom of negotiation and the principle of negotiation in good faith, where the principle of freedom of negotiation entails the freedom of the parties to enter into negotiations or not and the freedom to choose the form of negotiation. This freedom also extends to the freedom to choose the law applicable to the negotiation contract. But what restricts this freedom is the principle of negotiation in good faith. The latter requires that each negotiating party commit itself to good faith throughout the negotiating phase. This principle has several obligations, the most important of which are the obligation to cooperate and provide information. The obligation to preserve the confidentiality of information and the obligation to prohibit parallel negotiations and the violation of all negotiating obligations entails the determination of civil liability on the side of the breaching party. .................... الملخص: ترتكز مفاوضات عقود التجارة الدولية على العديد من المبادئ القانونية التي كرستها غالبية التشريعات المقارنة و كذا القواعد الدولية و ذلك بغية تنظيم العلاقة بين أطراف التفاوض، و أبرز هذه المبادئ هو مبدأ حرية التفاوض و مبدأ التفاوض بحسن نية حيث يترتب على مبدأ حرية التفاوض حرية الأطراف في الدخول في المفاوضات من عدمه و الحرية في اختيار شكل التفاوض. كما تمتد هذه الحرية أيضا لتشمل الحرية في اختيار القانون الواجب التطبيق على عقد التفاوض، لكن ما يقيد هذه الحرية هو مبدأ التفاوض بحسن نية حيث يقتضي هذا الأخير بأن يلتزم كل طرف متفاوض بحسن النية طيلة مرحلة المفاوضات كما يتفرع عن هذا المبدأ عدة إلتزامات أهمها الالتزام بالتعاون و تقديم المعلومات، الالتزام بالمحافظة على سرية المعلومات والالتزام بحظر المفاوضات الموازية و يترتب على مخالفة جميع الالتزامات التفاوضية تقرير المسؤولية المدنية في جانب الطرف المخل . .................... Résumé : Les négociations de contrats commerciaux internationaux sont basées sur de nombreux principes juridiques consacrés par la majorité des législations comparatives et les mêmes règles internationales afin de réglementer la relation entre les parties à la négociation de la liberté de négociation ", dont le plus important est le principe de liberté de négociation et le principe de négociation de bonne foi, lorsque le principe de la liberté de négociation implique la liberté des parties d’engager ou non des négociations et la liberté de choisir la forme de la négociation. Cette liberté s’étend également à la liberté de choisir la loi applicable au contrat de négociation. Mais ce qui limite cette liberté, c’est le principe de la négociation de bonne foi. Ce dernier exige que chaque partie aux négociations s’engage de bonne foi tout au long de la phase de négociation. Ce principe comporte plusieurs obligations, dont les plus importantes sont l’obligation de coopérer et de fournir des informations. L’obligation de préserver la confidentialité des informations et l’obligation d’interdire les négociations parallèles et la violation de toutes les obligations de négociation impliquent la détermination de la responsabilité civile du côté de la partie contrevenante.